ANALYSIS OF BALI PROVINCE'S FISHERY PRODUCT EXPORTS TO AUSTRALIA: A REVIEW UTILIZING TIME SERIES DATA FROM 2021-2024 - Anwar Anwar; Kurnia Sada Harahap; Muhammad Maskur; Budiyati Budiyati; Muhammad Rasnijal; Tri Ratna Saridewi; Diah Ayu Safitri; Mohammad Roin Najih; Nurdin Kasim (Jurnal Segara, 2026)
Fishery exports from Bali Province to Australia deserve specific analysis because Indonesia's fishery sector remains an important source of foreign exchange and non-oil and gas trade performance. This study seeks to evaluate the value and volume of Indonesian fisheries product exports to Australia from 2021 to 2024, emphasizing the effects of the Indonesia-Australia Comprehensive Economic Partnership Agreement (IA-CEPA) on these exports. The secondary data utilized encompasses the volume and value of exports for key commodities, including snapper, tuna, and pearls, sourced from the Fish Quarantine, Quality Control, and Safety of Fishery Products Center in Denpasar. A quantitative descriptive method employing time series trend analysis was utilized to depict monthly and annual variations and pinpoint turning points in Indonesian fisheries product exports. During 2021–2024, total exports reached 4,573,914.66 kg with a value of IDR 3,140,480,920,986.20. The highest export volume occurred in 2022 at 1,344,631.19 kg, while the highest export value occurred in 2024 at IDR 1,180,927,685,795.86. Compared with 2023, export value in 2024 increased by 119.05%, whereas volume increased by only 23.50%, indicating that the value increase was driven mainly by improved unit value and a shift toward higher-value commodities. Tuna contributed 41.35% of cumulative volume and 34.78% of cumulative value, while pearls contributed 27.38% of cumulative value with only 2.66% of cumulative volume. The number of commodity groups increased from 22 in 2021 to 27 in 2024. These findings indicate that Bali's export performance to Australia was shaped not only by volume expansion but also by commodity structure, product quality, and market diversification. IA-CEPA is therefore interpreted as a policy context that strengthens market access, rather than as the sole causal factor; further econometric testing is required to estimate its causal impact.